2010
DOI: 10.1186/1471-2458-10-400
|View full text |Cite
|
Sign up to set email alerts
|

Prejudice and misconceptions about tuberculosis and HIV in rural and urban communities in Ethiopia: a challenge for the TB/HIV control program

Abstract: BackgroundIn Ethiopia, where HIV and tuberculosis (TB) are very common, little is known about the prejudice and misconceptions of rural communities towards People living with HIV/AIDS (PLHA) and TB.MethodsWe conducted a cross sectional study in Gilgel Gibe Field Research area (GGFRA) in southwest Ethiopia to assess the prejudice and misconceptions of rural and urban communities towards PLHA and TB. The study population consisted of 862 randomly selected adults in GGFRA. Data were collected by trained personnel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
56
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(74 citation statements)
references
References 29 publications
13
56
5
Order By: Relevance
“…Place of residence did not show a significant association with attitudes of young women towards PLWHA in both countries. In contrast to the present finding, study in Bolivia, Botswana and Ethiopia showed different result [35,40,43]. The probability of acceptance attitude towards PLWHA increases with increasing level of education.…”
Section: Acceptance Attitude Of Young Women Towards Plwhacontrasting
confidence: 99%
See 1 more Smart Citation
“…Place of residence did not show a significant association with attitudes of young women towards PLWHA in both countries. In contrast to the present finding, study in Bolivia, Botswana and Ethiopia showed different result [35,40,43]. The probability of acceptance attitude towards PLWHA increases with increasing level of education.…”
Section: Acceptance Attitude Of Young Women Towards Plwhacontrasting
confidence: 99%
“…In this study the understanding of the young women about HIV/AIDS in Nigeria and DRC was found to be stable. Similar results were also reported in sub-Sahara Africa [33][34][35] and elsewhere [36]. However, despite the high level of awareness of HIV/AIDS, the Nigerian and Congolese young women had low level of knowledge.…”
Section: Awareness and Hiv/aids Knowledgesupporting
confidence: 86%
“…However, the patients in our study demonstrate a lack of knowledge about TB, once almost one half did not know how the disease was transmitted. Misconceptions about TB transmission have been reported in other studies 33 , and it is related to delays in diagnosis and treatment non-adherence 33,34,35,36 . We could not show an association between patient delay and lack of knowledge about TB, but is important to develop strategies to improve patient education about their illness in the TB services, since it can have implications in treatment adherence.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, showed that 40 -50% of the local population who suffering from HIV/AIDS are strongly discriminated. The discriminatory attitudes and stigmatization toward PLWHA in countries such as the UK (Ipsos MORI 2010) and Ethiopia (Aga et al 2009;Deribew et al 2010;Reilley et al 2004) were also reported.…”
Section: Discussionmentioning
confidence: 99%
“…For example, researches in Hong Kong reported discriminatory attitudes toward people with symptoms of HIV/AIDS among adults (Hong Kong AIDS Foundations 1996), teenagers (Davis, Noel, Chan & Wing 1998), workers (Lau & Ma 1995), Health service providers, (Lau & Lee 1996) and people at work (Lau & Wong 2001). Also, in countries such as the UK (Ipsos MORI 2010) and Ethiopia (Aga, Kylmä & Nikkonen 2009;Deribew et al 2010;Reilley, Hiwot & Mesure 2004), stigmatization and negative attitudes toward PLWHA have been reported. In Iran, several studies have shown negative attitudes about PLWHA (Etemad 2010;Rad, Hashemi & Alizadeh 2009;Sanei Moghaddam et al 2011;Sassani, Naji, Abedi & Taheri 2013) and also among nurses providing health care to PLWHA (Zeighami Mohamadi, Zeinali, Esmaily & Nikbakht Nasrabadi 2011).…”
Section: Introductionmentioning
confidence: 99%